Defining practical and robust study designs for interventions targeted at terrestrial mammalian predators - Khorozyan, Igor (Conservation biology : the journal of the Society for Conservation Biology, 2022)
© 2021 The Authors. Conservation Biology published by Wiley Periodicals LLC on behalf of Society for Conservation Biology.